Model dan Gaya Kepemimpinan yang Berhubungan dengan Motivasi Kerja serta Dampaknya terhadap Kinerja Pelayanan Prima Perawat Rawat Inap : A Scoping Review - Lucia Anniversary Simarmata; Ani Margawati; Septo Pawelas Arso (Universitas Pahlawan Tuanku Tambusai, 2026)
Background Inpatient nurses play a key role in maintaining healthcare service quality. High job demands require effective leadership to sustain nurses’ work motivation and ensure excellent service delivery. Objective To examine the relationship between leadership styles, nurses’ work motivation, and excellent service performance in inpatient settings. Methods This study employed a scoping review based on PRISMA guidelines. Thirteen national and international articles published between 2021 - 2025 were analyzed using narrative synthesis. Results Transformational, democratic, participative, and supportive leadership styles were positively associated with nurses’ work motivation. Work motivation acted as a mediating factor strengthening the relationship between leadership and excellent service performance, reflected in increased empathy, proactive behavior, and adherence to service standards. Conclusion Effective leadership significantly enhances nurses’ work motivation and excellent service performance. Leadership approaches emphasizing support and participation are essential to improve nursing service quality. Keywords: leadership style, work motivation, nursing performance, excellent service